Pre School selection system using Analytic Hierarchy Process (AHP): Implementation and Usability Study - Abd Rasid, Mamat; Mohamad Afendee, Mohamed; Norkhairaini, Abdul Rawi; Wan Suryani, Wan Awang; Fadhilah, Ahmad; Nurul Hanis, Abd Rasid (2017)
Pre-School education it is an important issue in modern family. Players in this field, whether private or government agencies, are trying to be the main operators for providing the best services. Selecting the best pre-schools put parents in dilemma due to the variety of options offered by the institutions. Parents are influenced by various factors such as fees, contents and facilities. However, parents have different preferences for their children education. The objectives of this research are to provide the main evaluation criteria for selection a pre-school and base on these criteria we will develop a system to assist parents in deciding the best choice for pre-school education. The system being developed took into consideration usability factor to decide users’ acceptance. In this research, two sets of questionnaires were distributed to the parents in order to gather data pertaining their perceptions. The results of the questionnaire were used in the system development process in which the Analytic Hierarchy Process (AHP) technique is integrated. User satisfaction towards the usability of the system has been proven through the results of the questionnaire in which System Usability Scale (SUS) was used. The system has been ranking from good to excellent in the score of 70%-80%.